Replacing Transanal Excision with Transanal Endoscopic Microsurgery and/or Transanal Minimally Invasive Surgery for Early Rectal Cancer - Hakiman, Hekmat; Pendola, Michael; Fleshman, James W. (Clinics in Colon and Rectal Surgery, 2015)
The use of local resection of rectal polyps and early rectal cancer has progressed to become the standard of care in most institutions with a colorectal surgery specialist. The use of transanal excision (TAE) with anorectal retractors and standard instrumentation has been supplanted by the application of endoscopic techniques which allow direct video augmented visualization. The transanal endoscopic microsurgery method provides a 3D view and works under a constant flow of air to keep the rectal vault open. Instruments capable of accomplishing a surgical excision and suture closure work through a long 4 cm tube set at the anal canal. The newest version of TAE is transanal minimally invasive surgery which is similar to a single-site laparoscopic technique using a hand access port at the anal canal to maintain a seal for insufflation of the rectum, regular 2D video camera for visualization, and laparoscopic instrumentation through the port in the anus. Each of these techniques is described in detail and the outcomes compared, which show the progress being made in this area of colorectal surgery.
Keywords: local excision of rectal cancer; transanal endoscopic microsurgery; transanal excision; transanal minimally invasive surgery